An unorthodox way to confirm an uncommon complication of central venous catheter placement - Kugasia, Irfanali Rajabali; Ijaz, Mohsin; Khan, Ahsan (Journal of Emergency and Critical Care Medicine, 2019)
Malpositioning of central venous catheters (CVC) is a common complication and easily identified on a chest X-ray (CXR). However, positioning of CVC in the pleural space without causing pneumothorax is extremely rare and difficult to identify on a single view CXR. Pleural placement of CVC can be suspected by: either presence of pneumothorax post insertion or being able to flush ports of the CVC but without blood return.